LITERARY REVIEW ON THE ANTECEDENT OF ETHICAL DILEMMA IN MANAGEMENT ACCOUNTING PROFESSION - Ferdianto Dwiputra; Elia Mustikasari (Universitas Airlangga, 2021)
This study aims to: 1) Describe a model expounding the inception of ethical dilemma management accountants are exposed to, delving to its antecedents; and 2) Formulate a strategy to combat ethical dilemma experienced by management accountants. The data is collected through literary study. Data analysis process is descriptive-andqualitative in nature, consisting of data explication, data reduction, and concluding inference. The result showed that ethical dilemma of management accountants was rooted by two antecedent factors: internal and external. One of the many strategies to combat it and to produce ethical decisions was to orient one’s intention to ethical deeds. The intent was affected by three elements, which were attitude towards behaviour, subjective norms, and perceived behavorial control. This study is expected to be a source of inspiration and strategy for management accountants in dealing with ethical dilemmas in decision making related to their profession. Its academic implications, hence, hopefully will be of an enriching and useful reference for accounting profession ethics study, as well as inspiring a deeper interest in research management accounting ethics.